Reason in Revolt : Dialectical Philosophy and Modern Science. - Woods, Ted (Algora Pub., 2007)
Two of Britain's deans of socialist thought consider the philosophical writings of Marx and Engels in the light of recent advances in the sciences. The authors have written a dozen books; this work is a hit in ten countries. The book reasserts the dialecti.